Magnetic Properties of Well-Aligned ZnO Nanorod Arrays Grown by a Simple Hydrothermal Reaction - Jiangni Yun; Rui Qu; Zhiyong Zhang; Jun Li (Advances in Condensed Matter Physics)
Well-aligned ZnO nanorod arrays with room temperature ferromagnetism were prepared on glass substrate through hydrothermal method. The as-prepared nanorod arrays were characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), energy dispersive spectroscopy (EDS), photoluminescence (PL) spectrum, and magnetization measurements. The XRD and SEM results indicated that the ZnO nanorods are with the wurtzite structure and exhibit preferential (002) orientation with c-axis perpendicular to the substrate surface. The PL results suggested that the possible defect in the as-prepared ZnO nanorod arrays might be VZn, Oi, or OZn. The first-principles calculations reveal that the room temperature ferromagnetism may result from the VZn defects present in the ZnO nanorod and the hybridization of the Zn 3d states with O 2p states is responsible for the half-metallic ferromagnetism in ZnO nanorod.